Spatial associations between infestations of mountain pine beetle and landscape features in the Peace River Region of British Columbia. - de la Giroday, Honey-Marie C. (Author); Aukema, Brian (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2010)
An immense outbreak of the mountain pine beetle, Dendroctonus ponderosae Hopkins, currently covers a cumulative area of 14.5 million hectares of mature pine forests across the provinces of British Columbia and Alberta, Canada. In 2004, the first outbreaking populations of mountain pine beetle were observed in northeastern British Columbia, an area not considered part of the insect's native range. My thesis examines how landscape features and their orientation influence establishment patterns of the insect. Mountain pine beetle spread between 2004 and 2006 in patterns similar to a propagating wave, likely due to long-distance dispersal into the region. Large glacially-eroded valleys, canyons, deeply incised streams, local and midslope ridges or small hills in valleys and plains, and open slopes were often positively associated with infestations, providing evidence that the interaction of meso-scale convective currents and topography can mediate patterns of establishment. The orientation of landscape features also influenced establishment, as southwest-facing areas and linear features aligned in northeast-southwest directions were associated with increased densities of infestations in 2006. Management activities were typically associated with a decline in the density of mountain pine beetle infestations in the following year, indicating that such activities were effective in preventing short-distance dispersal of the insect. I found no evidence that anthropogenic activities such as transport and storage of infested material increased establishment of mountain pine beetle across the research area. These results may be used to prioritize preemptive treatments in mountainous regions in the absence of long-distance inputs of mountain pine beetle into expanding ranges. --P.ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1646700